1999
DOI: 10.1118/1.598627
|View full text |Cite
|
Sign up to set email alerts
|

Iterative image warping technique for temporal subtraction of sequential chest radiographs to detect interval change

Abstract: A temporal subtraction technique has been developed to assist radiologists in the detection of interval changes on chest radiographs. Although the overall performance of the current temporal subtraction technique is relatively good, severe misregistration errors, mainly due to AP inclination and/or rotation, are observed in some cases. In order to reduce these errors, we attempted to improve the subtraction scheme by applying an iterative image warping technique. In cases obtained with the new temporal subtrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(47 citation statements)
references
References 9 publications
0
47
0
Order By: Relevance
“…The registered image is subtracted and if the registration is successful, areas with interval change appear as either dark or bright on a gray background. The original technique has been improved and evaluated using subjective ratings by radiologists of the quality of the subtraction image [110,113] and the results of the method have been compared with manual registration [131]. An observer study [56] with a small number of selected cases showed an increase in detection accuracy of interval change when both the normal image and the subtraction image were presented to the radiologist.…”
Section: Subtraction Techniquesmentioning
confidence: 99%
“…The registered image is subtracted and if the registration is successful, areas with interval change appear as either dark or bright on a gray background. The original technique has been improved and evaluated using subjective ratings by radiologists of the quality of the subtraction image [110,113] and the results of the method have been compared with manual registration [131]. An observer study [56] with a small number of selected cases showed an increase in detection accuracy of interval change when both the normal image and the subtraction image were presented to the radiologist.…”
Section: Subtraction Techniquesmentioning
confidence: 99%
“…An imagewarping technique such as that described in the "Appendix" is first applied to the current and the previous image, as shown in Figure 1a,b, respectively, in order to obtain shift vectors 5 which represent the extent of deformation (or warping) of the previous image relative to the current image. Based on these shift vectors on the current image, the previous image can be warped to produce a temporal subtraction image.…”
Section: -D Nonlinear Image Warping By Use Of 3-d Voxel Matching Andmentioning
confidence: 99%
“…Many warping techniques for two-dimensional (2-D) images in chest radiography have been developed in the field of computer-aided diagnosis. 1,[3][4][5][6][7] In the temporal subtraction obtained with multipledetector computed tomography (MDCT) volume images that is used in thoracic examinations, it is necessary to employ a more complex threedimensional (3-D) registration and warping of lung regions between the current and previous images.…”
mentioning
confidence: 99%
“…Ishida et al added to this method an initial global matching found through cross correlation of two radiographs at low resolution 8 and later extended the algorithm to include iterative steps. 9 Armato et al employed the same algorithm in the subtraction of temporally sequential DE soft-tissue images. 10 Other applications involve registering ventilation-perfusion images with digital chest radiography using contour detection and anatomical landmarks.…”
Section: Introductionmentioning
confidence: 99%